Qualitative inquiry into premarital sexual behaviours and contraceptive use among multiethnic young women: implications for education and future research - Wong, L.P. (Public Library of Science, 2012)
Background: This study was a qualitative investigation into sexual attitudes and behaviours, and contraceptive use among Malaysian youth, based on constructs from the health belief model, theory of reasoned action, and problem behaviour theory. Methods: A total of 34 focus group discussions with 185 participants were conducted among the Malay (35), Chinese (34), and Indian (31) young females between November, 2010 and April, 2011. The participants were secondary school students and university undergraduates from Selangor and the Federal Territory of Kuala Lumpur. Results: The study found a lack of knowledge about sexual issues and contraception among the participants. Many engaged in unprotected sexual intercourse and relied on periodic abstinence, natural methods, and traditional folk pregnancy preventive practices. The findings also revealed numerous categories of factors influencing sexual attitudes and behaviours: ethnic group and religion, level of religiosity, peer pressure and norms, and parental monitoring. With regard to condom use, factors such as embarrassment about condom acquisition, low perceived susceptibility to sexually transmitted infections (STIs), and perceived efficacy of traditional and folk methods of contraception, were uncovered from the discussions. Conclusion: This study underscores the importance of development of culturally specific interventions that address the identified promoting factors of premarital sex. Behavioral interventions to promote condom use should increase awareness about condom effectiveness against not only unwanted pregnancies but also STIs. Citation: Wong LP (2012) Qualitative Inquiry into Premarital Sexual Behaviours and Contraceptive Use among Multiethnic Young Women: Implications for Education and Future Research. PLoS ONE 7(12): e51745. doi:10.1371/journal.pone.0051745